2015
DOI: 10.1080/10400435.2015.1030514
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Vertical Pole Configuration and Location on Assisting the Sit-to-Stand Movement in Older Adults with Mobility Limitations

Abstract: The evaluation of vertical pole configuration and location on assisting the sit-to-stand movement in older adults with mobility limitations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The proposed approach realizes the biomechanical phenomenon of joint torques being generated by active and passive tension forces coactivated in skeletal muscles and the correlation between muscle activation and joint torques (Lomaglio and Eng, 2005 ; Vena et al, 2015 ; Jones, 2017 ). It was suggested that larger joint torques are reflected by muscles in greater activation.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed approach realizes the biomechanical phenomenon of joint torques being generated by active and passive tension forces coactivated in skeletal muscles and the correlation between muscle activation and joint torques (Lomaglio and Eng, 2005 ; Vena et al, 2015 ; Jones, 2017 ). It was suggested that larger joint torques are reflected by muscles in greater activation.…”
Section: Methodsmentioning
confidence: 99%
“…Yet the females rated the activity as ‘somewhat severe’ compared to the ‘severe’ rating of the males. The perception of STS will impact mobility at rehabilitation or home as it is a precursor to most mobility activities (Vena et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%